Report of the Working Group on Research, Education, Training, Capacity Building and Information Management for the Environment and Forests Sector for the Eleventh Five Year Plan (2007-2012) - Planning Commission (Planning Commission, 2014)
Indian Environment and Forests Sector is facing major challenges in the fast changing global and Indian scenario. It requires no less a revolutionary approach than the ‘green’ or ‘white’ revolution. The key environmental challenges that the country faces relate to the nexus of environmental degradation with poverty in many dimensions, and economic growth. Further, The role of forests in poverty alleviation, providing goods and services to the society, ensuring environmental security of the country and promoting carbon sequestration has assumed much greater importance than ever before. There are a number of other important ecosystems lying outside the traditional boundaries of the forests which require direct or indirect interventions of foresters in association with other stakeholders. The Research and Development (R&D) strategy has to take into account conservation and sustainable management of forests and forest production possibilities outside forests. We need a Common Research and Development Agenda.
Government of India, Planning Commission
Government of India, Planning Commission